2021
DOI: 10.1177/03915603211014864
|View full text |Cite
|
Sign up to set email alerts
|

Can we use neutrophil to lymphocyte ratio in the diagnosis and prediction of extracapsular extension in localized prostate cancer?

Abstract: Purpose: We investigated role of neutrophil-to-lymphocyte ratio (NLR) in the diagnosis and prediction of extracapsular extension (ECE) in clinically localized prostate cancer (PCa). Materials and methods: A total of 396 patients with clinically localized PCa who underwent open radical retropubic prostatectomy (RRP), and 260 patients with benign prostatic hyperplasia (BPH) who underwent suprapubic prostatectomy were included in the study. Preoperative NLR, prostate specific antigen (PSA), prostate specific anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In fact, this can reflect the role of machines in the clinic; that is, machine diagnosis is an assistant to clinicians and not a replacement for radiologists. The ECE stage with different anatomic sites of invasion indicates the aggressiveness of the primary tumor 23,24 . To better understand the effects of LiSNet on prognosis, we also explored survival in grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this can reflect the role of machines in the clinic; that is, machine diagnosis is an assistant to clinicians and not a replacement for radiologists. The ECE stage with different anatomic sites of invasion indicates the aggressiveness of the primary tumor 23,24 . To better understand the effects of LiSNet on prognosis, we also explored survival in grades.…”
Section: Discussionmentioning
confidence: 99%
“…The ECE stage with different anatomic sites of invasion indicates the aggressiveness of the primary tumor. 23,24 To better understand the effects of LiSNet on prognosis, we also explored survival in grades. We found that OS was lower in patients with high-defect capsule appearance scaled by LiSNet, showing that staging capsular appearance with AI is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%